Hubungan Antara Dukungan Sosial dan Kualitas Hidup pada Remaja Berkebutuhan Khusus - Diah Ayu Novita; Resnia Novitasari (Universitas Katolik Soegijapranata, 2017)
The aim of the study is to understand the relationship between social support and quality of life in adolescent with special needs. The hypothesis in this study that there was a relationship between social support and quality of life in adolescent with special needs. The study sample involves 63 subject from special needs school Sleman and special needs school Bantul in Yogyakarta which consist 37 males and 26 females within age range 11 – 18 years old. The measuring tool of this study are adopted Multidimensional Scale of Perceived Social Support from Zimet, Dahlem, Zimet & Farley (1988) and translastion from Youth Quality Of Life Instrument – Short Form (YQOL-SF) Version 2.0 from Edwards, Huebner, Connel and Patrick (2002). The data analisys of this study was using Product Moment Pearson. Based on the result, it shows that there is a significant relationship between social support and quality of life in adolescent with special needs. (r = 0,264 and p = 0,018, p